Pengaruh Diversifikasi Pangan Terhadap Peningkatan Kualitas Gizi: Strategi Menuju Ketahanan Pangan dan Kesehatan - Putri Andita, Destira; Sabaha, Ahmad; Amilia, Laila; Salza Alya Sabila, Ratu; Irpani, Khoirul; Desmawan, Deris (Teewan Journal Solutions, 2025)
Food diversification is one form of human effort to diversify food availability. Food diversification can help realize food independence, reduce dependence on food imports, and improve the quality of community nutrition. However, not all humans can fulfill their food needs, making it difficult to diversify food. This study aims to analyze food diversification policies in influencing the improvement of people's nutritional quality. This research was conducted using quantitative and descriptive methods. The existence of food diversification policies cannot be separated from demographic, socio-cultural and economic factors of farming households. Research Results.